2009
DOI: 10.1016/j.genm.2009.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Gender as a determinant of responses to a self-screening questionnaire on anxiety and depression by patients with coronary artery disease

Abstract: Background-Because patients with coronary artery disease (CAD) could benefit from interventions to decrease psychological distress, it is important to identify these individuals. Both salivary cortisol level and the Hospital Anxiety and Depression Scale (HADS) are recognized measures of stress/anxiety and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Authors compared the means of the subscales of anxiety and depression and found a higher score of anxiety among women than among men: 5.3 and 3.3, respectively (p=0.03). In relation to depression, the mean scores of women were also higher (3.8 for females and 2.5 for males, p = 0.07) (22) .…”
Section: Discussionmentioning
confidence: 89%
“…Authors compared the means of the subscales of anxiety and depression and found a higher score of anxiety among women than among men: 5.3 and 3.3, respectively (p=0.03). In relation to depression, the mean scores of women were also higher (3.8 for females and 2.5 for males, p = 0.07) (22) .…”
Section: Discussionmentioning
confidence: 89%
“…One study found that the HAS score, but not the HDS score, correlated positively with the cortisol awakening response among patients with coronary artery disease [34]. Another study among patients with coronary artery disease found that the HDS score correlated positively with salivary cortisol in men, but not in women, while in women, but not in men, the HAS score correlated negatively with salivary cortisol [35]. In patients with low back pain, HADS scores were unrelated to the diurnal cortisol rhythm measured in saliva [36], while in the normal population, HADS scores were inversely associated with peak salivary cortisol during a psychological stress protocol [37].…”
Section: Discussionmentioning
confidence: 99%
“…7 Studies have demonstrated that patients undergoing cardiac catheterization experience anxiety coming not only from the fact that the experience of catheterization is unknown, but also from uncertainty about the catheterization findings. 8 The wait time before the procedure may cause even more anxiety than the procedure itself. 6,9 Anxiety produced before and during the catheterization can increase myocardial oxygen demand and place greater stress on the heart.…”
mentioning
confidence: 99%
“…6,9 Anxiety produced before and during the catheterization can increase myocardial oxygen demand and place greater stress on the heart. 8 Decreasing cardiac catheterization anxiety can be a key factor in improving the outcome. Anxiety is consistently characterized by a pattern of reciprocal inhibition between sympathetic activation and vagal deactivation.…”
mentioning
confidence: 99%